Improvement of Anticancer Drug Release by Cobalt Ferrite Magnetic Nanoparticles through Combined pH and Temperature Responsive Technique. Issue 21 (20th September 2018) - Dey, Chaitali; Ghosh, Arup; Ahir, Manisha; Ghosh, Ajay; Goswami, Madhuri Mandal
Abstract: This work reports the application possibilities of cobalt ferrite (CoFe2 O4 ) magnetic nanoparticles (CFMNPs) for stimuli responsive drug delivery by magnetic field induced hyperthermia technique. The CFMNPs were characterized by X‐ray diffraction (XRD) with Rietveld analysis, field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), selected area electron diffraction (SAED), fourier transform infrared spectroscopy (FTIR), thermogravimetry and differential thermal analysis (TG‐DTA), vibrating sample magnetometer (VSM) and superconducting quantum interference device (SQUID) magnetometry. Particles were functionalized with folic acid (FA) by EDC‐NHS coupling method and loaded with anticancer drug (DOX) by activated folate ions. The drug release was studied as a function of time at two different temperatures (37 and 44 °C) under pH∼5.5 and 7. It was observed that the drug release rate is higher at elevated temperature (44 °C) and acidic pH∼5.5 as compared to our normal body temperature and pH∼7 using the CFMNPs. This way, we have developed a pH and temperature sensitive drug delivery system, which can release the anticancer drug selectively by applying ac magnetic field as under ac field particles are heated up. We have calculated the amount of heat generation by the particles around 1.67 °C per second at ∼600 Hz frequency. By MTT assay on cancer cell and normal cell, it was confirmed that CFMNPs are nontoxic and biocompatible in nature, which assures that our synthesized particles can be successfully used in localized cancer treatment by stimuli responsive drug delivery technique. Abstract : Improved drug release is achieved using folic acid functionalized cube shaped cobalt ferrite magnetic nanoparticles (CFMNPs) at low pH (5.5) and high temperature (44 °C). By modulating the pH, the loading and detachment of a cancer drug from the surface of the functionalized CFMNPs can be managed. Thermal agitation also improves the release of drugs.